Interocular Difference in Retinal Nerve Fiber Layer Thickness Predicts Optic Neuritis in Pediatric-Onset Multiple Sclerosis. Issue 4 (December 2021) - Waldman, Amy T.; Benson, Leslie; Sollee, John R.; Lavery, Amy M.; Liu, Geraldine W.; Green, Ari J.; Waubant, Emmanuelle; Heidary, Gena; Conger, Darrel; Graves, Jennifer; Greenberg, Benjamin
Abstract : Background: Optical coherence tomography (OCT) is capable of quantifying retinal damage. Defining the extent of anterior visual pathway injury is important in multiple sclerosis (MS) as a way to document evidence of prior disease, including subclinical injury, and setting a baseline for patients early in the course of disease. Retinal nerve fiber layer (RNFL) thickness is typically classified as low if values fall outside of a predefined range for a healthy population. In adults, an interocular difference (IOD) in RNFL thickness greater than 5 μm identified a history of unilateral optic neuritis (ON). Through our PERCEPTION (PEdiatric Research Collaboration ExPloring Tests in Ocular Neuroimmunology) study, we explored whether RNFL IOD informs on remote ON in a multicenter pediatric-onset MS (POMS) cohort. Methods: POMS (defined using consensus criteria and first attack <18 years) patients were recruited from 4 academic centers. A clinical history of ON (>6 months prior to an OCT scan) was confirmed by medical record review. RNFL thickness was measured on Spectralis machines (Heidelberg, Germany). Using a cohort of healthy controls from our centers tested on the same machines, RNFL thickness <86 μm (<2 SDs below the mean) was defined as abnormal. Based on previously published findings in adults, an RNFL IOD >5 μm was defined as abnormal. The proportions of POMS participants with RNFL thinning (<86 μm) and abnormal IOD (>5 μm) were calculated. Logistic regression was used to determine whether IOD was associated with remote ON. Results: A total of 157 participants with POMS (mean age 15.2 years, SD 3.2; 67 [43%] with remote ON) were enrolled. RNFL thinning occurred in 45 of 90 (50%) ON eyes and 24 of 224 (11%) non-ON eyes. An IOD >5 μm was associated with a history of remote ON ( P < 0.001). An IOD >5 μm occurred in 62 participants, 40 (65%) with remote ON. Among 33 participants with remote ON but normal RNFL values (≥86 μm in both eyes), 14 (42%) were confirmed to have ON by IOD criteria (>5 μm). Conclusions: In POMS, the diagnostic yield of OCT in confirming remote ON is enhanced by considering RNFL IOD, especially for those patients with RNFL thickness for each eye in the normal range. An IOD >5 μm in patients with previous visual symptoms suggests a history of remote ON.